2008
DOI: 10.1016/j.jcv.2008.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of detection of respiratory viruses in the lower respiratory tract of hospitalized adults

Abstract: This study shows a high prevalence of viruses in the lower respiratory tract samples of hospitalized adults, mostly HRV and FLU-A. It is not possible to establish the role of viruses detected at low frequency, but our findings suggest the necessity to consider them as potential causes or precursors of lower respiratory tract infections (LRTIs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 43 publications
6
27
1
Order By: Relevance
“…Increasing evidence suggests that virus infection in LRTI patients has been underestimated [3,15,30,31,32,33,34,35]. Our data are in agreement with previous studies which were based on virus isolation and culture from bronchoalveolar lavage samples, PCR results from throat swabs and/or serology [3,36,37].…”
Section: Discussionsupporting
confidence: 92%
“…Increasing evidence suggests that virus infection in LRTI patients has been underestimated [3,15,30,31,32,33,34,35]. Our data are in agreement with previous studies which were based on virus isolation and culture from bronchoalveolar lavage samples, PCR results from throat swabs and/or serology [3,36,37].…”
Section: Discussionsupporting
confidence: 92%
“…The importance of the specimen type is highlighted in several studies. In BAL specimens a diagnostic yield ranging from 3.6% to 32.0% was reported [15][16][17]. Soccal et al evaluated paired nasopharyngeal and BAL fluid specimens and observed an overall viral positivity rate of 29.3% in the upper respiratory tract specimens and 17.2% in the BAL samples (P < 0.001) [18].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of respiratory viral infections (RVIs) in immunocompetent adults is often overlooked; however, available data suggest that RVIs are responsible for a significant number of respiratory infections affecting not only the elderly (persons aged ≥65 years) but also young adults. 12,13,[27][28][29][30][31][32] Although the majority of infections in young adults are not life-threatening they can impose a significant burden on communities since the affected population represents a large fraction of the work force in developing countries. Data presented in this report indicate that 65.1% (28/43) of virus-positive samples were detected in patients <60 years of age.…”
Section: Discussionmentioning
confidence: 99%